PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN RUMAH SAKIT - Erdayan Muhlishulamal; Sofa Parihah Nurasiah (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study examines the influence of transformational leadership style and organizational culture on employee productivity in the nursing division of Rumah Sakit (RS) Rumah Sehat Terpadu (RST) Dompet Dhuafa Bogor. The research employed a quantitative method with descriptive and verification approach, involving 126 respondents from a population of 185 nursing staff. Data collection utilized structured questionnaires with a 5-point Likert scale, while data analysis employed multiple linear regression techniques. The findings revealed that transformational leadership demonstrated a positive and significant impact on employee productivity with a contribution of 32.1%, while organizational culture contributed 20.9%. Simultaneously, both variables significantly influenced employee productivity with a combined contribution of 53.1%. The idealized influence dimension scored highest in transformational leadership, while team orientation emerged as the strongest aspect of organizational culture. Employee productivity showed good performance overall, particularly in work enthusiasm. The study concludes that effective leadership practices and supportive organizational culture are crucial determinants in enhancing nursing productivity. Organizations should focus on strengthening transformational leadership development programs and cultivating employee-oriented cultural practices to optimize workforce performance in healthcare settings.